Overview of Hepatitis B Virus Exposure on NAT and CLIA Blood Examination Methods at PMI Semarang City - Rina Puspita (International Journal of Seocology, 2021)
There are 421 blood bank in Indonesia, only 12 blood bank used NAT method to test transfusion transmitted disease. Whereas NAT is a moleculer test is recommended by WHO to detect window period. These study is to describe transfusion transmitted disease using NAT and CLIA method on exposure to Hepatitis B virus in Red Cross Semarang City periode April-December 2019. The result of NAT and CLIA are diviaded to two groups, reactive or non-reactive on exposure of Hepatiti B virus. The method used in this research is a descriptived method which is analyzed with univariat. The variabel was obtained from medical record from Red Cross Semarang city which consist of reactive or nonreactive in NAT and CLIA as much 6.931 population. The samples used in this study are 100 samples, using the purposive sampling technique with predefined criteria. In 100 samples, we found 19 reactive test with NAT methods, 17 reactive test with NAT and CLIA and finally found 64 non reactive with NAT and CLIA. From the population of 6.931, only 36 is reactive with NAT only, or both NAT and CLIA (19 reactive on NAT methods and 17 reactive on NAT and CLIA methods). As the result only 0,5% is reactive, so NAT and CLIA are important test for blood safety requirements.